The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/microorganisms11071822
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Organic Compound Assessment as a Screening Tool for Early Detection of Gastrointestinal Diseases

Abstract: Gastrointestinal (GI) diseases have a high prevalence throughout the United States. Screening and diagnostic modalities are often expensive and invasive, and therefore, people do not utilize them effectively. Lack of proper screening and diagnostic assessment may lead to delays in diagnosis, more advanced disease at the time of diagnosis, and higher morbidity and mortality rates. Research on the intestinal microbiome has demonstrated that dysbiosis, or unfavorable alteration of organismal composition, precedes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 134 publications
0
1
0
Order By: Relevance
“…Another study showed changes in the urine VOC spectrum, indicating limited data on the impact of intestinal preparation on VOC generation in the body. Dalis et al [112] believed that dysbiosis or adverse changes in the composition of the organism appear before the clinical symptoms of various gastrointestinal diseases appear. Research into the diagnosis of gastrointestinal disease has led to a shift toward non-invasive methods for gastrointestinal screening, including chemical detection tests that measure changes in VOCs.…”
Section: Detection Of Intestinal Diseasesmentioning
confidence: 99%
“…Another study showed changes in the urine VOC spectrum, indicating limited data on the impact of intestinal preparation on VOC generation in the body. Dalis et al [112] believed that dysbiosis or adverse changes in the composition of the organism appear before the clinical symptoms of various gastrointestinal diseases appear. Research into the diagnosis of gastrointestinal disease has led to a shift toward non-invasive methods for gastrointestinal screening, including chemical detection tests that measure changes in VOCs.…”
Section: Detection Of Intestinal Diseasesmentioning
confidence: 99%
“…In recent years, a series of studies have proposed novel methods, such as the diagnosis of BAD through the detection of volatile organic compounds (VOCs) produced by gut microbiota metabolism. By analyzing the VOCs, the status of the gut microbiota can be inferred, allowing for the assessment of bile acid metabolism and subsequent diagnosis of BAD [73][74][75][76]. By conducting bacteriome analysis and volatile gas testing on both BAD patients and healthy individuals, it is possible to identify distinguishing features.…”
Section: Detecting Intestinal Microbiota and Its Metabolitesmentioning
confidence: 99%